Green regionalism in world trade law - HSIEH, Pasha L. (Institutional Knowledge at Singapore Management University, 2025)
Multifaceted geopolitical conflicts have led to disruptions in the trade regime and multilateral negotiations. As a paradigm shift, green regionalism has emerged as a new normative process for regional economic frameworks to integrate and operationalize environmental sustainability. The article offers the first interdisciplinary analysis of green regionalism in world trade law. It argues that green regionalism, which has evolved amid various waves of global regionalism, constructs the normative foundation for 'Trade and Sustainability 2.0'. The article employs the concept of recognition in international relations to unveil the motivations and actions of major states in catalyzing green regionalism. Legal and political challenges confronting the Environmental Goods Agreement of the World Trade Organization, environmental agreements, and mega-trade agreements are also examined. Second, the article explores the multipolar frameworks for implementing green regionalism. Case studies involving recent developments of US and EU trade pacts, as well as of new Asia-Pacific green economy agreements, shed light on the trade-sustainability nexus. Hence, the theoretical and empirical implications of the research are valuable for devising trade law approaches to advancing Sustainable Development Goals.